2015
DOI: 10.3389/fpls.2015.00089
|View full text |Cite
|
Sign up to set email alerts
|

Fructan biosynthesis and degradation as part of plant metabolism controlling sugar fluxes during durum wheat kernel maturation

Abstract: Wheat kernels contain fructans, fructose based oligosaccharides with prebiotic properties, in levels between 2 and 35 weight % depending on the developmental stage of the kernel. To improve knowledge on the metabolic pathways leading to fructan storage and degradation, carbohydrate fluxes occurring during durum wheat kernel development were analyzed. Kernels were collected at various developmental stages and quali-quantitative analysis of carbohydrates (mono- and di-saccharides, fructans, starch) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…Combining expression responses under two important environmental cues, i.e., N-starvation and cold-treatment, and two hormonal cues (ABA, ethylene precursor ACC) signaling drought (ABA) and water logging (ACC), respectively, this study provides insight into the dynamic regulation of source-to-sink sugar transport and fructan metabolism, and indicates that at whole plant level petioles display gene expression profiles distinct from leaf blade and taproot, respectively. Although enzyme activities were not determined, previous studies on chicory (Van Laere and Van den Ende, 2002) and on durum wheat (Cimini et al, 2015) have shown that FAZY expression at transcript level largely correlates with corresponding enzyme activities, suggesting that fructan enzymes are mainly controlled at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Combining expression responses under two important environmental cues, i.e., N-starvation and cold-treatment, and two hormonal cues (ABA, ethylene precursor ACC) signaling drought (ABA) and water logging (ACC), respectively, this study provides insight into the dynamic regulation of source-to-sink sugar transport and fructan metabolism, and indicates that at whole plant level petioles display gene expression profiles distinct from leaf blade and taproot, respectively. Although enzyme activities were not determined, previous studies on chicory (Van Laere and Van den Ende, 2002) and on durum wheat (Cimini et al, 2015) have shown that FAZY expression at transcript level largely correlates with corresponding enzyme activities, suggesting that fructan enzymes are mainly controlled at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Total fructans were measured according to Morcuende et al (2004). Fructan classes were determined according to Cimini et al (2015). Starch and total fructans were expressed as glucose equivalents.…”
Section: Methodsmentioning
confidence: 99%
“…The unusual topology of the XdINV dimer suggests the possibly that it might be able to accommodate a putative polymeric substrate as it could be a mixed fructan with branched ␤(2-1)/ ␤(2-6) linkages (42,43) that, indeed, is degraded by XdINV. Fructans present in plants are a mixture of heterogeneous oligomers and polymers with a composition depending on the environment and the development state of the plant (38).…”
Section: Discussionmentioning
confidence: 99%